2010
DOI: 10.1016/j.jadohealth.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Bullying Among Adolescents in the Growing Up Today Study

Abstract: Purpose-To examine the relationship between sexual orientation and past-year reports of bullying victimization and perpetration in a large sample of American youth.Methods-Survey data from 7,559 adolescents aged 14 to 22 who responded to the 2001 wave questionnaire of the Growing Up Today Study were examined cross-sectionally. Multivariable generalized estimating equations regression was performed using the modified Poisson method. We examined associations between sexual orientation and past-year bully victimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
205
2
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(239 citation statements)
references
References 36 publications
14
205
2
18
Order By: Relevance
“…Previous research has investigated bullying, such as physical or verbal abuse, with regards to sexual orientation (Berlan et al 2010, Mishna et al 2009, Pilkington and D'Augelli 1995, Swearer et al 2008). These studies have indicated that those who identify as non-heterosexual are at a higher risk of victimisation than others.…”
Section: Bullying Amongst Lgbt Youthmentioning
confidence: 99%
“…Previous research has investigated bullying, such as physical or verbal abuse, with regards to sexual orientation (Berlan et al 2010, Mishna et al 2009, Pilkington and D'Augelli 1995, Swearer et al 2008). These studies have indicated that those who identify as non-heterosexual are at a higher risk of victimisation than others.…”
Section: Bullying Amongst Lgbt Youthmentioning
confidence: 99%
“…Sexual minority youth and those perceived to be LGB have repeatedly been found to experience school bullying at significantly higher rates than heterosexual students (Berlan, Corliss, Field, Goodman, & Austin, 2010;Kessel Schneider, O'Donnell, Stueve, & Coulter, 2012;O'Malley-Olsen, Kann, Vivilo-Kantor, Kinchen, & McManus, 2014;Williams, Connolly, Pepler, & Craig, 2005). Indeed, much school bullying often takes the form of homophobic teasing and slurs, regardless of whether it is directed at self-identified LGB youth or not (Poteat & Rivers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 One population that may be at an increased risk of misusing AAS is sexual minority (gay and bisexual) boys. Sexual minorities are at an increased risk for a variety of maladaptive outcomes, including substance use, [8][9][10] depression, 11 victimization, [12][13][14] suicidality, 9,11,15 and body image dissatisfaction. 16 There are likely a number of reasons to explain these health disparities, with one prominent theory being the sexual minority stress model.…”
mentioning
confidence: 99%